2023
DOI: 10.1021/acs.jctc.3c00617
|View full text |Cite
|
Sign up to set email alerts
|

Toward Benchmark-Quality Ab Initio Predictions for 3d Transition Metal Electrocatalysts: A Comparison of CCSD(T) and ph-AFQMC

Hagen Neugebauer,
Hung T. Vuong,
John L. Weber
et al.

Abstract: Generating accurate ab initio ionization energies for transition metal complexes is an important step toward the accurate computational description of their electrocatalytic reactions. Benchmark-quality data is required for testing existing theoretical methods and developing new ones but is complicated to obtain for many transition metal compounds due to the potential presence of both strong dynamical and static electron correlation. In this regime, it is questionable whether the so-called gold standard, coupl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 157 publications
2
22
0
Order By: Relevance
“…As an empirical functional, ωB97M-D4 has many parameters that were tailored to a specific (default) ω value, which might hamper the applicability of optimal tuning (a discussion of this is provided in the Supporting Information). While any final conclusions regarding the robustness of ωB97M-D4 concerning variations in ω clearly require many further tests beyond NCIs, recent studies appear to confirm that optimal tuning of ωB97M-D4 and related functionals improves the performance for various properties. ,, Nevertheless, caution is generally advisable when functionals, empirical or not, are applied with nondefault parameters, as illustrated by the poor performance of LC-BLYP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As an empirical functional, ωB97M-D4 has many parameters that were tailored to a specific (default) ω value, which might hamper the applicability of optimal tuning (a discussion of this is provided in the Supporting Information). While any final conclusions regarding the robustness of ωB97M-D4 concerning variations in ω clearly require many further tests beyond NCIs, recent studies appear to confirm that optimal tuning of ωB97M-D4 and related functionals improves the performance for various properties. ,, Nevertheless, caution is generally advisable when functionals, empirical or not, are applied with nondefault parameters, as illustrated by the poor performance of LC-BLYP.…”
Section: Resultsmentioning
confidence: 99%
“…This global empirical parameter is typically obtained by fitting to appropriate thermochemistry and kinetics data sets like GMTKN55 or MGCDB84 . However, in certain situations, the performance in ground and excited-state calculations can be improved by a molecule-specific nonempirical optimal tuning of the range-separation parameter ω. This also applies to empirical functionals, i.e., those parametrized against large databases, like ωB97M-D4 studied here. , Recent studies have demonstrated much-improved performance in combination with optimal tuning for ground and excited states. , Further considerations regarding the optimal tuning of empirical functionals can be found in the Supporting Information.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The behavior of the phaseless bias is difficult to quantify, and thus, the vast majority of studies to date focus on benchmarking ph-AFQMC with different trials in order to devise strategies to obtain increasingly accurate benchmark results on difficult systems at minimal cost. Such approaches have been largely successful, with calculations using multireference trials performing well on many transition metal complexes for which single-reference methods such as coupled cluster (CC) can fail. …”
Section: Introductionmentioning
confidence: 99%